Metal alloy powder material for wear-resistant layer of loop roller of finishing mill and preparation method of wear-resistant layer

By using a gradient coating composed of iron-based alloy and WC on the looper rolls of the finishing mill, the performance problems of the looper rolls under harsh working conditions such as high temperature, wear, impact and corrosion have been solved, and the service life of the looper rolls has been significantly improved.

CN120984874APending Publication Date: 2025-11-21TAIER (ANHUI) IND TECH SERVICE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511193472.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-25
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

The service life of existing finishing mill loop rolls is relatively short. Traditional materials and manufacturing methods are difficult to meet their performance requirements under harsh working conditions such as high temperature, wear, impact and corrosion, resulting in high replacement frequency and affecting the production efficiency of steel plants.

Method used

A gradient coating, including a transition layer and a wear-resistant layer, is formed by laser cladding using a metal alloy powder material composed of iron-based alloy and WC. The material composition and process parameters are optimized to improve the strength and durability of the coating.

Benefits of technology

It significantly improves the service life of the rolling mill looper rolls, reduces the replacement frequency, increases rolling efficiency, and reduces operating costs, with a lifespan increase of 2-3 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120984874A_ABST
    Figure CN120984874A_ABST
Patent Text Reader

Abstract

The invention discloses a metal alloy powder material for a wear-resistant layer of a loop roller of a finishing mill. The metal alloy powder material is composed of 85%-90% by mass of iron-based alloy and 10%-15% by mass of a WC material. The iron-based alloy material comprises the following chemical components in percentage by mass: 15-18% of Cr, 0.6-1.3% of Mo, 1-1.6% of Ni, 1-2% of Si, 1-2% of B, 0.1-0.2% of Nb, 0.15-0.3% of Ti, less than or equal to 0.25% of C and the balance of Fe. The metal alloy powder material disclosed by the invention has excellent comprehensive properties such as wear resistance, corrosion resistance, impact resistance, high temperature resistance, cold and hot fatigue resistance, adhesion resistance and the like. Meanwhile, the invention further provides a preparation method of the wear-resistant layer of the loop roller of the finishing mill, the total thickness of the coating is increased by adopting the gradient coating subjected to laser cladding, the strength of the coating is improved, and the crushing phenomenon is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of material surface modification, and in particular to a metal alloy powder material for the wear-resistant layer of a hot-rolled finishing mill looper roll and its processing method. Background Technology

[0002] In recent years, my country's steel industry has developed rapidly. Steel companies have further improved their production capacity and rolling efficiency through internal technological and equipment upgrades. Meanwhile, the proportion of specialty steel, silicon steel, and high-strength steel has also increased. With the increase in steel mill rolling efficiency and output, and the change in rolled steel grades, working conditions have become increasingly harsh. Consequently, the service life of looper rolls has gradually decreased, the replacement frequency has gradually increased, and consumption has risen rapidly. However, due to the steel industry's development and the requirements for cost reduction and efficiency improvement, customers have increasingly higher quality requirements for finishing mill looper rolls. Looper rolls manufactured using traditional materials and methods have short service lives and high replacement frequency, severely restricting the rapid development of steel mills. Therefore, how to improve the service life of finishing mill looper rolls has become a pressing problem for manufacturers and a strong expectation of customers. After hot-rolled slabs exit the heating furnace and pass through roughing and descaling, their temperature reaches as high as 900℃~1050℃ when passing through the finishing mill's looper rolls. Therefore, the roll surface temperature of the looper rolls is extremely high during operation. Simultaneously, the strip travels at a relatively high speed, typically 2~25m / s depending on the slab thickness, and the looper rolls need to provide tension. Consequently, the looper rolls must withstand significant impact and frictional wear. Therefore, the finishing mill's looper rolls require excellent high-temperature resistance, wear resistance, and impact resistance. Furthermore, the looper rolls are cooled internally by water and externally by sprayed water reflecting off the rebounding strip, which further demands higher requirements on their resistance to thermal fatigue and corrosion.

[0003] Because the working conditions of the rolling mill's looper rolls are extremely harsh, they are prone to wear, thermal fatigue cracks, and even coating peeling during use. Researching and developing new materials and new manufacturing methods to improve their service life will inevitably play an important role in increasing production and efficiency for steel enterprises.

[0004] The main methods to improve the service life of the looper rolls of finishing mills include integral casting, wear-resistant alloy overlay welding, and nickel-based alloy spraying. Each of these methods has the following disadvantages: Integral casting involves adding some high-alloy materials during the casting of the looper roll blank, which is costly; the overlay welding process has large heat input, large deformation, and large dilution rate, requiring multiple layers of overlay welding to reduce the impact. In addition, the preheating required before welding further increases the heat input, resulting in coarse grains in the alloy layer and a significant reduction in performance; nickel-based materials sprayed are easily worn and peeled off under large impact loads, and the material is expensive and has a short service life. At the same time, it is very easy to cause steel sticking problems in stainless steel production lines.

[0005] Since the above methods are insufficient for the actual use of looper rolls, laser cladding has become one of the most important methods. Currently, the wear-resistant layer of finishing mill looper rolls is usually formed by cladding with Cr16 series materials. Its disadvantages are: 1. Cr16 series stainless steel itself has poor wear resistance and anti-adhesion properties; 2. The wear-resistant layer is directly clad on the outside of the substrate without a transition layer: 1. It is easy to produce insufficient dilution strength, and the coating is prone to crushing due to impact during use; 2. The base material of the looper roll is carbon steel with low hardness (below HB200). The difference in the coefficient of thermal expansion between the Cr16 series stainless steel cladding layer and the base material is large, which makes it easy to crack under high temperature and thermal fatigue conditions. Summary of the Invention

[0006] The problem this invention aims to solve is to provide a metal alloy powder material for the wear-resistant layer of finishing mill looper rolls, which possesses excellent comprehensive properties such as wear resistance, corrosion resistance, impact resistance, high temperature resistance, thermal fatigue resistance, and anti-adhesion properties. Simultaneously, this invention also provides a method for preparing the wear-resistant layer of finishing mill looper rolls, which increases the total coating thickness and improves coating strength by employing a gradient coating with laser cladding, thus preventing crushing.

[0007] The present invention relates to a metal alloy powder material for the wear-resistant layer of the slip roll of a finishing mill, which is composed of 85% to 90% by mass of an iron-based alloy and 10% to 15% by mass of WC material; wherein the chemical composition and mass percentage of the iron-based alloy material are: 15% to 18% Cr, 0.6% to 1.3% Mo, 1% to 1.6% Ni, 1% to 2% Si, 1% to 2% B, 0.1% to 0.2% Nb, 0.15% to 0.3% Ti, ≤0.25% C, and the balance being Fe.

[0008] The preferred chemical composition and mass percentage of the iron-based alloy material are: 18% Cr, 1.3% Mo, 1.6% Ni, 1% Si, 1% B, 0.1% Nb, 0.15% Ti, 0.25% C, with the balance being Fe.

[0009] The preferred chemical composition and mass percentage of the iron-based alloy material are: 17% Cr, 1.1% Mo, 1.3% Ni, 1.5% Si, 1.1% B, 0.12% Nb, 0.18% Ti, 0.25% C, with the balance being Fe.

[0010] The preferred chemical composition and mass percentage of the iron-based alloy material are: 16% Cr, 1.2% Mo, 1.3% Ni, 1.4% Si, 1.1% B, 0.15% Nb, 0.2% Ti, 0.25% C, with the balance being Fe.

[0011] The metal alloy powder material used for the wear-resistant layer of the finishing mill looper roll of the present invention is a mechanically mixed powder; wherein, the iron-based alloy has a particle size of 53μm-150μm and the WC has a particle size of 45μm-150μm; after the iron-based alloy and WC powder are mixed in the required proportion, they are uniformly stirred and mixed in a ball mill for no less than 3 hours.

[0012] The present invention discloses a method for manufacturing a wear-resistant layer on a finishing mill looper roll, comprising the following steps: ① Rough machining: machining the looper roll blank according to the drawings, wherein the roll surface is turned to be 4mm smaller than the final size; ② Pre-cladding flaw detection: performing colorimetric and ultrasonic flaw detection on the machined looper roll surface to ensure that the roll body is free from external and internal defects such as cracks, pores, and inclusions; ③ Laser cladding: the cladding layer comprises two layers: the transition layer is a conventional iron-based alloy material, and the outer wear-resistant layer is the material of the present invention; ④ Post-cladding machining: turning followed by grinding, and finally fine grinding the roll surface to the dimensional tolerances and roughness of the drawings; ⑤ Finished product flaw detection: performing colorimetric and magnetic particle flaw detection on the finely ground finishing mill looper roll to ensure that the roll is free from defects such as cracks and pores.

[0013] In step ③, laser cladding, the chemical composition and mass percentage of the transition layer material are: 15-19% Cr, 1-3% Mo, 4-7% Ni, 1-2% Si, 0.8-1.5% B, 0.2-0.6% Nb, <0.1% C, with the balance being Fe. The process parameters for the transition layer cladding are: rectangular spot size 19mm × 3.7mm, laser power 4-5kW, scanning speed 8-12mm / s, powder feeding rate 40-55g / min, and overlap rate 35%-50%.

[0014] In step ③, laser cladding, the wear-resistant layer needs to be preheated before cladding, with a preheating temperature of 200-300℃.

[0015] In step ③, laser cladding, the process parameters for cladding the wear-resistant layer are: rectangular spot size 19mm×3.7mm, laser power 4.8~5.6kW, scanning speed 7~10mm / s, powder feeding rate 55~80g / min, and overlap rate 35%~50%.

[0016] The transition layer has a design thickness of 0.9–1.1 mm, and the wear-resistant layer has a design thickness of 1.6–1.8 mm.

[0017] The principle and effect of the metal alloy powder material and wear-resistant layer process for the wear-resistant layer of the finishing mill looper roll of this invention are as follows: I. Gradient coating of transition layer + wear-resistant layer: The physical properties of the 45 steel base of the looper roll, the transition layer material (conventional iron-based alloy), and the wear-resistant layer alloy material (iron-based alloy + WC) are shown in Table 1. It can be seen that the density, melting point, and coefficient of thermal expansion of the wear-resistant layer alloy material are basically close to those of the transition layer iron-based alloy and the 45 steel base material: 1. During the cladding process, due to the small difference in the coefficient of thermal expansion between the coating and the base material... 1. The resulting thermal stress is small, enabling the preparation of a cladding layer without crack defects; 2. The substrate, transition layer, and wear-resistant layer have similar densities, melting points, and coefficients of thermal expansion. The use of a transition layer to separate the wear-resistant layer from the substrate reduces C dilution. Furthermore, both the transition layer and wear-resistant layer alloys contain certain amounts of Ni and Mo, as well as trace amounts of Nb, resulting in excellent resistance to thermal fatigue; 3. The wear-resistant layer material readily undergoes solute flow in the molten pool formed by laser irradiation, leading to the formation of carbides (Cr23C6, Ti...) in the cladding layer. The uniform and dispersed distribution of carbides (such as C) can significantly improve wear resistance and hardness uniformity; and the carbides still have high hardness at high temperatures, which can meet the working conditions of the looper rolls; II. Wear-resistant layer materials: 1. Iron-based alloy: iron-based self-fluxing alloy: 1-2% B, 1-2% Si, the main purpose is to lower the melting point of the alloy, thereby forming a low-melting-point eutectic, and at the same time, it can generate hard phases such as CrB, so that the hardness and wear resistance of the coating after cladding can be improved to a certain extent; 15-18% Cr can improve the corrosion resistance of the coating, and a certain amount of Cr element can form a Cr2O3 protective layer on the surface of the cladding layer, improving the coating's resistance to high-temperature oxidation, thus meeting the high operating temperature requirements of the looper rolls of the finishing mill; 2. WC phase can further improve its wear resistance on the one hand, and improve the coating's resistance to foreign matter adhesion on the other hand, preventing steel adhesion phenomenon. However, as the amount added increases, the coating becomes more brittle, so an appropriate amount needs to be added. Studies have found that when the WC content is 10-15%, its comprehensive performance is optimal.

[0018] Table 1 Physical properties, wear-resistant layer alloy, and transition layer iron-based alloy of 45# steel

[0019] Material <![CDATA[Density (g / cm 2 )]]> Melting point (°C) <![CDATA[Coefficient of thermal expansion (10 -6 K -1 )]]> Wear-resistant layer alloy 7.85 1255 11.0 Transition layer iron-based alloy 7.85 1248 11.3 45 steel 7.85 1495 11.6

[0020] Therefore, the wear-resistant metal alloy material of this invention, through the individual and combined effects of multiple elements, possesses excellent comprehensive properties such as wear resistance, corrosion resistance, impact resistance, high temperature resistance, thermal fatigue resistance, and anti-adhesion performance. Simultaneously, this material has a wide processing window and good machinability, significantly reducing the probability of cladding defects such as cracks during the cladding process. Furthermore, this invention employs a gradient coating cladding design method (transition layer + wear-resistant layer), i.e., cladding the transition layer first and then the wear-resistant layer. The transition layer serves two purposes: firstly, it acts as a transitional barrier to reduce dilution of the substrate; secondly, it has a hardness of over 35 HRC, increasing the total coating thickness and improving coating strength, thus preventing crushing.

[0021] Therefore, the finishing mill looper rolls manufactured using the gradient coating laser cladding of the metal alloy material of this invention exhibit excellent comprehensive mechanical and performance properties, with a significantly extended service life. Actual online use verification in steel plants has shown that their service life is 2-3 times longer than that of rolls manufactured using traditional methods such as surfacing, integral casting, spray welding of nickel-based alloys, and conventional cladding. The long service life of the finishing mill looper rolls produced by this invention reduces replacement frequency, improves rolling efficiency and line output, and lowers overall operating costs. Attached Figure Description

[0022] Figure 1 This is a schematic diagram of the finishing mill looper roll prepared according to the present invention;

[0023] Figure 2 This is a metallographic photograph of the wear-resistant cladding layer of the present invention. Detailed Implementation

[0024] To better understand this invention, the materials and preparation methods of this invention will be further described in detail below with reference to specific examples.

[0025] Example 1

[0026] When the base material of the looper roller is 45# steel and the roller specifications are... At that time, the processing method is as follows:

[0027] ① Rough machining: The looper roll blank is machined according to the drawings, wherein the outer diameter of the roll surface is machined to the specified dimensions.

[0028] ② Flaw detection before cladding: Colorimetric and ultrasonic flaw detection are performed on the surface of the machined looper roll to ensure that the roll body is free of external and internal defects such as cracks, pores, and inclusions.

[0029] ③ Laser cladding: First, clad the transition layer, cladding 0.9mm on one side; then clad the wear-resistant layer, cladding 1.8mm on one side; the wear-resistant layer needs to be preheated to 300℃ before cladding.

[0030] ④ Post-cladding processing: first turn, then grind, and finally finish grinding the roller surface to...

[0031] ⑤ Finished product flaw detection: Colorimetric and magnetic particle flaw detection are performed on the precision-ground rolling mill looper rolls to ensure that the rolls are free of defects such as cracks and pores.

[0032] In step ③, the cladding transition layer has the following chemical composition and mass percentage: 19% Cr, 3% Mo, 7% Ni, 1.3% Si, 0.9% B, 0.3% Nb, 0.05% C, with the balance being Fe; the process parameters are: rectangular spot size 19mm × 3.7mm, laser power 4.6kW, scanning speed 8mm / s, powder feeding rate 42g / min, and overlap rate 37%.

[0033] In step ③, the cladding wear-resistant layer consists of a material comprising 85% iron-based alloy and 15% WC by mass. The chemical composition and mass percentage of the iron-based alloy are as follows: 18% Cr, 1.3% Mo, 1.6% Ni, 1% Si, 1% B, 0.1% Nb, 0.15% Ti, 0.25% C, with the balance being Fe. The process parameters are: rectangular spot size 19mm × 3.7mm, laser power 5.6kW, scanning speed 7mm / s, powder feeding rate 62g / min, and overlap rate 47%.

[0034] Example 2

[0035] When the base material of the looper roller is Q355 and the roller specifications are... At that time, the processing method is as follows:

[0036] ① Rough machining: The looper roll blank is machined according to the drawings, wherein the outer diameter of the roll surface is machined to the specified dimensions.

[0037] ② Flaw detection before cladding: Colorimetric and ultrasonic flaw detection are performed on the surface of the machined looper roll to ensure that the roll body is free of external and internal defects such as cracks, pores, and inclusions.

[0038] ③ Laser cladding: First, clad the transition layer, cladding 1.0 mm on one side; then clad the wear-resistant layer, cladding 1.7 mm on one side; the wear-resistant layer needs to be preheated to 250℃ before cladding.

[0039] ④ Post-cladding processing: first turn, then grind, and finally finish grinding the roller surface to...

[0040] ⑤ Finished product flaw detection: Colorimetric and magnetic particle flaw detection are performed on the precision-ground rolling mill looper rolls to ensure that the rolls are free of defects such as cracks and pores.

[0041] In step ③, the cladding transition layer has the following chemical composition and mass percentage: 18% Cr, 2% Mo, 6% Ni, 1.5% Si, 1% B, 0.4% Nb, 0.05% C, with the balance being Fe; the process parameters are: rectangular spot size 19mm × 3.7mm, laser power 4.7kW, scanning speed 8mm / s, powder feeding rate 43g / min, and overlap rate 42%.

[0042] In step ③, the cladding wear-resistant layer consists of a material comprising 87% iron-based alloy and 13% WC material by mass. The chemical composition and mass percentage of the iron-based alloy material are as follows: 17% Cr, 1.1% Mo, 1.3% Ni, 1.5% Si, 1.1% B, 0.12% Nb, 0.18% Ti, 0.25% C, with the balance being Fe. The process parameters are: rectangular spot size 19mm × 3.7mm, laser power 5.5kW, scanning speed 7mm / s, powder feeding rate 58g / min, and overlap rate 47%.

[0043] Example 3

[0044] When the base material of the looper roller is 20# steel and the roller specifications are... At that time, the processing method is as follows:

[0045] ① Rough machining: The looper roll blank is machined according to the drawings, wherein the outer diameter of the roll surface is machined to the specified dimensions.

[0046] ② Flaw detection before cladding: Colorimetric and ultrasonic flaw detection are performed on the surface of the machined looper roll to ensure that the roll body is free of external and internal defects such as cracks, pores, and inclusions.

[0047] ③ Laser cladding: First, clad the transition layer, cladding 1.1mm on one side; then clad the wear-resistant layer, cladding 1.6mm on one side; the wear-resistant layer needs to be preheated to 200℃ before cladding.

[0048] ④ Post-cladding processing: first turn, then grind, and finally finish grinding the roller surface to...

[0049] ⑤ Finished product flaw detection: Colorimetric and magnetic particle flaw detection are performed on the precision-ground rolling mill looper rolls to ensure that the rolls are free of defects such as cracks and pores.

[0050] In step ③, the cladding transition layer has the following chemical composition and mass percentage: 17% Cr, 1.5% Mo, 5.5% Ni, 1.5% Si, 1% B, 0.5% Nb, 0.05% C, with the balance being Fe; the process parameters are: rectangular spot size 19mm × 3.7mm, laser power 4.8kW, scanning speed 8mm / s, powder feeding rate 47g / min, and overlap rate 43%.

[0051] In step ③, the cladding wear-resistant layer consists of a material comprising 90% iron-based alloy and 10% WC material by mass. The chemical composition and mass percentage of the iron-based alloy material are as follows: 16% Cr, 1.2% Mo, 1.3% Ni, 1.4% Si, 1.1% B, 0.15% Nb, 0.25% C, 0.2% Ti, with the balance being Fe. The cladding process parameters are: rectangular spot size 19mm × 3.7mm, laser power 5.4kW, scanning speed 7mm / s, powder feeding rate 60g / min, and overlap rate 43%.

[0052] The alloy composition design of the transition layer and wear-resistant layer in the above embodiments is based on the following: the production line used for this looper roll product is a hot continuous rolling line, which operates at high temperatures, is subject to water corrosion, and suffers from uneven heating and cooling; at the same time, the roll surface is subjected to significant impact and friction from the strip steel, resulting in extremely severe wear. Therefore, selecting materials capable of forming carbide-reinforcing phases and adding a certain proportion of WC can further improve the coating's wear resistance and resistance to foreign matter adhesion; the alloy is selected with a higher Cr element and a comparable Mo element value, which improves the corrosion resistance of the cladding layer and ensures a certain high-temperature strength for the coating.

[0053] To better verify the effectiveness of the materials and cladding method of this invention, samples of the cladding layer prepared using the materials and process methods of this invention were taken and subjected to corresponding performance tests, and compared with weld overlay coatings, spray-welded nickel-based alloy samples, and conventional Cr16 cladding coatings. The experiments mainly included a 550℃ wear test to test its wear resistance, a 900℃ oxidation test to test its high-temperature oxidation resistance, an impact test to test its impact resistance, and a thermal shock test (the sample was heated to a red-hot state and then instantly immersed in cold water, repeatedly cyclically until cracks appeared). The wear test was conducted on a high-temperature end-face friction and wear testing machine at a test temperature of 550℃, using Al2O3 as the friction pair, and the wear volume was obtained using a laser confocal microscope. The oxidation test involved heating the sample to 900℃, holding it at that temperature for 24 hours, allowing it to cool naturally to room temperature, and then weighing it to measure the weight gain after oxidation. The test results are shown in Table 2.

[0054] Table 2 Comparison of performance of different coatings

[0055]

[0056]

[0057] As can be seen from Table 2, the finishing mill loop rolls made using the materials and methods of this invention have significantly improved wear resistance, high temperature resistance, impact resistance, and thermal fatigue resistance compared to surfacing, spraying nickel-based alloys, and conventional Cr16 cladding coatings. After evaluation in online use, its service life is increased by about 2 to 3 times compared to the other methods mentioned above.

[0058] The structure of the looper rollers obtained in Examples 1-3 is as follows: Figure 1 As shown, Figure 2 The image shows a metallographic photograph of the wear-resistant cladding layer of the present invention: the white round particles are WC hard particles, and the white strip-shaped objects are carbide (Cr23C6, TiC, etc.) alloy phases. As can be seen from the image, the WC particles and carbide alloy phases are uniformly and dispersedly distributed in the molten pool, which can significantly improve the wear resistance and hardness uniformity of the substrate.

[0059] The metal alloy powder material of this invention is not limited to the application on the surface of the finishing mill looper roll. Theoretically, it can be applied to the surface of all parts that are in the same or similar working conditions as the finishing mill looper roll to improve the service life of the parts.

Claims

1. A metal alloy powder material for the wear-resistant layer of the rolling mill looper rolls, characterized in that: It consists of 85%–90% iron-based alloy and 10%–15% WC material by mass; wherein the chemical composition and mass percentage of the iron-based alloy material are: 15–18% Cr, 0.6–1.3% Mo, 1–1.6% Ni, 1–2% Si, 1–2% B, 0.1–0.2% Nb, 0.15–0.3% Ti, ≤0.25% C, and the balance is Fe.

2. The metal alloy powder material according to claim 1, characterized in that: The preferred chemical composition and mass percentage of the iron-based alloy material are: 18% Cr, 1.3% Mo, 1.6% Ni, 1% Si, 1% B, 0.1% Nb, 0.15% Ti, 0.25% C, with the balance being Fe.

3. The metal alloy powder material according to claim 1, characterized in that: The preferred chemical composition and mass percentage of the iron-based alloy material are: 17% Cr, 1.1% Mo, 1.3% Ni, 1.5% Si, 1.1% B, 0.12% Nb, 0.18% Ti, 0.25% C, with the balance being Fe.

4. The metal alloy powder material according to claim 1, characterized in that: The preferred chemical composition and mass percentage of the iron-based alloy material are: 16% Cr, 1.2% Mo, 1.3% Ni, 1.4% Si, 1.1% B, 0.15% Nb, 0.2% Ti, 0.25% C, with the balance being Fe.

5. The metal alloy powder material according to claim 1, characterized in that: The metal alloy powder material is a mechanically mixed powder; wherein, the iron-based alloy has a particle size of 53μm-150μm and the WC has a particle size of 45μm-150μm; after the iron-based alloy and WC powder are mixed in the required proportion, they are uniformly stirred and mixed in a ball mill for no less than 3 hours.

6. A method for preparing the wear-resistant layer of the looper rolls of a finishing mill, comprising the following steps: ① Rough machining: Machining the looper roll blank according to the drawings, wherein the roll surface is turned to be 4mm smaller than the final size; ② Flaw detection before cladding: Colorimetric and ultrasonic testing are performed on the surface of the machined looper roll to ensure that the roll body is free of external and internal defects such as cracks, pores, and inclusions. ③ Laser cladding: The cladding layer consists of two layers: a transition layer made of conventional iron-based alloy material and an outer wear-resistant layer made of the metal alloy powder material described in claims 1-4; ④ Post-cladding processing: first turn, then grind, and finally fine grind the roller surface to the dimensional tolerances and roughness specified in the drawing; ⑤ Finished product flaw detection: Colorimetric and magnetic particle flaw detection are performed on the precision-ground rolling mill looper rolls to ensure that the rolls are free of defects such as cracks and pores.

7. The preparation method according to claim 6, characterized in that: In step ③ laser cladding: the chemical composition and mass percentage of the transition layer material are: 15-19% Cr, 1-3% Mo, 4-7% Ni, 1-2% Si, 0.8-1.5% B, 0.2-0.6% Nb, <0.1% C, with the balance being Fe; the process parameters for transition layer cladding are: rectangular spot size 19mm × 3.7mm, laser power 4-5kW, scanning speed 8-12mm / s, powder feeding rate 40-55g / min, and overlap rate 35%-50%.

8. The preparation method according to claim 6, characterized in that: Step ③ Laser cladding: The wear-resistant layer needs to be preheated before cladding. The preheating temperature is 200-300℃.

9. The preparation method according to claim 6, characterized in that: In step ③ laser cladding: the process parameters for cladding the wear-resistant layer are: rectangular spot size 19mm×3.7mm, laser power 4.8~5.6kW, scanning speed 7~10mm / s, powder feeding rate 55~80g / min, and overlap rate 35%~50%.

10. The preparation method according to claim 6, characterized in that: The design thickness of the transition layer is 0.9–1.1 mm, and the design thickness of the wear-resistant layer is 1.6–1.8 mm.